Analisis Nilai-nilai Karakter dalam Buku Cerita Suku Penunggang Layang-layang sebagai Alternatif Muatan Media Pembelajaran - Elis Listiani; Eva Alviani; Ratih Dwi Setiawati (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
The importance of inculcating character values to children, especially in elementary schools, can have an impact on the development of the character that is in them. This character learning can be done in various ways, one of which is through story books. Currently, there are many story books in circulation, one of which is the storybook of Suku Penunggang Layang-layang by Tere Liye. This book contains many character values that can be used as a source of character learning in children. This study uses a qualitative approach with content analysis methods with data analysis techniques from Miles and Huberman. The results of the analysis that have been carried out show that in the story book of Suku Penunggang Layang-layang there are 11 character values out of 18 character values according to the Ministry of Education and Culture, namely; 1) hard work as much as 4 pieces of the story. 2) discipline as much as 4 fragments of the story, 3) independent as much as 2 fragments of the story, 4) honest as much as 6 fragments of the story, 5) social care as much as 12 fragments of the story, 6) responsibility as much as 3 fragments of the story, 7) curiosity as much as 6, 8) confident as many as 9 story fragments, 9) appreciating achievements as many as 11 story fragments, 10) helping as many as 6 story fragments, and 11) national spirit as much as 3 story fragments. Furthermore, the results of the analysis of character values in this book can be used as an alternative media of learning in elementary schools, in the form of zigzag book.